THE EFFECT OF SERVICE QUALITY, PRICE, AND TASTE IMAGE ON CONSUMER SATISFACTION AT GHATHAF PREMIUM COFFEE, PANTE KEC. SYAMTALIRA ARON REGENCY - Sumarni; Hamdiah; Ikrammuddin; Siti Maimunah (RADJA PUBLIKA, 2025)
This study aims to find out how the effect of service quality, price, and taste on consumer satisfaction at Ghathaf Coffee Premium, Pante Kec.Syamtalira Aron, North Aceh Regency partially. This study uses primary data obtained through the distribution of questionnaires to 126 respondents. The questionnaire instrument was tested through validity tests and reliability tests with Cronbach's Alpha approach. To test the feasibility of the regression model, a series of classical assumption tests were carried out which included normality tests, multicollinearity tests, and heteroscedasticity tests. Hypothesis testing was carried out using a t-test (partial) and coefficient of determination (R²) analysis. The data analysis technique used in this study is multiple linear regression analysis with the help of SPSS version 23 software. The results of the study show that the Service Quality variable has a significance value of 0.005 and a tcal value of 2.844 > ttable, which is 1.657 which means that it has a positive and significant effect on Consumer Satisfaction. Thus, the first hypothesis is accepted. Meanwhile, the Price variable has a significance value of 0.027 and a calculation of 2.243 > table, which means it has a positive and significant influence on Consumer Satisfaction, so the second hypothesis is accepted. Furthermore, the Taste variable showed a significance value of 0.009 and a calculation of 2.672 > ttable which means it has a positive and significant influence on Consumer Satisfaction, so the third hypothesis is accepted. Thus, it can be concluded that the partial influence of service quality, price, and taste on Consumer satisfaction has a positive and significant influence.